Hormone-producing Ovarian Tumors in Children. Literature Review - Elena V. Sibirskaya; Irina V. Karachentsova; Angelina A. Sysoeva; Mariia Yu. Chernysheva; Kristina A. Osmanova; Evgenia G. Kotikova (Union of pediatricians of Russia, 2024)
Hormone-producing ovarian tumors in girls are an actual problem in modern gynecology, which is associated with certain difficulties in managing patients. Firstly, it is worth taking into account the higher anatomical mobility of tumors in girls than in adults, due to the high location of the ovaries, weakness of the ligamentous apparatus and the active lifestyle of the child, which causes a higher incidence of torsion of the volumetric mass in children. Secondly, surgical treatment of hormone-producing ovarian tumors leads to a decrease in ovarian reserve and irreversible consequences in the reproductive health of patients in the future, which is an extremely undesirable complication in childhood. Therefore, methods of fertility preservation should be discussed with girls and their parents. It is also important to note that hormone-producing ovarian tumors have a certain degree of malignancy and a tendency to recur. Thus, the relevance of this topic lies in the complexity of management of pediatric patients with this pathology due to the clinical features of the course and a higher probability of complications. Hormone-producing ovarian masses should also include follicular cysts and corpus luteum cysts, but the above structures are excluded from the discussion in this article.